(untitled) (Zoological Archives: An International Journal, 2026)
Amphibians comprise the most threatened vertebrate class, yet the deep phylogenetic relationships among major amphibian clades – and the timing of their major diversification events – remain incompletely resolved, limiting comparative analyses of the biological traits that predict vulnerability and the evolutionary origins of susceptibility to chytridiomycosis. This study assembled a phylogenomic dataset of 3,240 ultraconserved element (UCE) loci and 284 single-copy nuclear genes from 124 amphibian species representing all three orders (Gymnophiona: 18 species; Caudata: 48 species; Anura: 58 species) plus 16 tetrapod outgroups, including 28 newly sequenced transcriptomes from taxonomically critical lineages. Concatenated maximum likelihood (IQ-TREE; 4,924,840 bp supermatrix) and coalescent species tree analyses (ASTRAL-III; 3,240 gene trees) converged on a well-supported topology resolving Gymnophiona as sister to Batrachia (Caudata + Anura; bootstrap 98%, gCF = 64.8%). Relaxed clock divergence time estimation (MCMCtree; 22 fossil calibrations) placed the Lissamphibia crown at 324 +/- 14 Ma and recovered a Triassic origin of all three modern orders (Gymnophiona 248 +/- 12 Ma; Caudata 234 +/- 10 Ma; Anura 218 +/- 10 Ma). Concordance factor analysis identified 8 nodes with gene tree discordance attributable to incomplete lineage sorting during rapid Cretaceous-Paleogene diversification. Ancestral state reconstruction identified direct development (loss of free-living larval stage) as having evolved independently at least 14 times within Anura, with strong correlation with terrestrial microhabitat specialisation. These results provide the most comprehensively resolved amphibian phylogeny to date and a dated framework for macroevolutionary analyses of amphibian diversification, trait evolution, and vulnerability to extinction.